Fighting Militants in Pakistan: Who Is In Charge? - James, Michael Dorsey (2016)
A lethal attack on a Pakistani police academy in Quetta, the provincial capital of Baluchistan, highlights the country’s power struggle over policy towards militant Saudi-backed Islamist groups nurtured by the Pakistan military and intelligence service. It also spotlights China’s willingness to accommodate Pakistani ambivalence towards militants.